Financial development and inequality: Brazil 1985-1994 - Manoel Bittencourt (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
We examine the impact of financial development on earnings inequality in Brazil in the 1980s and first half of the 1990s. The evidence based on panel-time series data and analysisshows that financial development had a significant and robust effect in reducing inequality during the period. We suggest that this is not only because the poorer can invest the acquired credit in either short or long-term productive activities, but also because those with access to financial markets can insulate themselves against recurrent poor macroeconomic performance, which is exemplified by high rates of inflation. The main implication of the results is that a deeper and more active financial sector, alleviates the high inequality seen in Brazil without distorting economic efficiency.
Keywords: D31; E44; O11; O54; 330; Finanzsektor; Entwicklung; Einkommensverteilung; Brasilien